2019
DOI: 10.1074/jbc.ra118.005527
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor TFAP2B up-regulates human corneal endothelial cell–specific genes during corneal development and maintenance

Abstract: The corneal endothelium, which originates from the neural crest via the periocular mesenchyme (PM), is crucial for maintaining corneal transparency. The development of corneal endothelial cells (CECs) from the neural crest is accompanied by the expression of several transcription factors, but the contribution of some of these transcriptional regulators to CEC development is incompletely understood. Here, we focused on activating enhancer-binding protein 2 (TFAP2, AP-2), a neural crest-expressed transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…The resulting small AP2α-positive colonies of cells surrounded by a thick cell mass that had clear similarities with CEnCs caught our attention. Due to the importance of the AP2 family to CEn development [ 31 ], we pursued to find a method to increase the amount of these cells. Surprisingly, discarding BMP inhibition from the protocol had the highest impact on the yield of AP2α-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting small AP2α-positive colonies of cells surrounded by a thick cell mass that had clear similarities with CEnCs caught our attention. Due to the importance of the AP2 family to CEn development [ 31 ], we pursued to find a method to increase the amount of these cells. Surprisingly, discarding BMP inhibition from the protocol had the highest impact on the yield of AP2α-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Resent studies showed that TFAP2B as one of the corneal endothelial-specific transcription factors 29 , and identified ZP4 as a target gene of TFAP2B, TFAP2B could bind to the ZP4 promoter region and directly induce the expression of the ZP4 protein 30 . In our study, TFAP2B expression was high in papillary thyroid cancer cell lines compared with normal cells and in tumor tissues compared with tissues adjacent to tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The third wave of mesenchymal cell migration also contributes to iris formation (Eghrari et al, 2015 ). PITX2 and FOXC1 are key transcription factors expressed in the periocular mesenchyme regulating corneal development; mutations in these genes are associated with anterior segment dysgenesis (Hara et al, 2019 ). PAX6 expression is still critical at this point for the development of the anterior segment structures originating from the mesenchyme (Cvekl and Tamm, 2004 ; see Supplementary Table S3 for a comprehensive overview of the genes associated with development eye disorders).…”
Section: Developmental Eye Disorders and Associated Genetic Variants mentioning
confidence: 99%